Change and continuity in biotechnology and new materials innovation: The evolution of technologies, markets and institutions. (4th August 2014) - Chataway, Joanna; Wield, David
This paper examines R&D and strategic decision–making in firms, reviewing institutional and market constraints that act on the development of bio– and new materials technologies. The findings are assessed against the background of biotechnology and new materials as potential 'core technologies' that, combined with new socioeconomic norms, will make up a significantly different technoeconomic paradigm for the next century. The studies presented portray levels of complexity that highlight the variety of technological evolution. They also illustrate the need for improved methods of analysis that better integrate macro– and micro–levels of evolutionary theory.